Facile preparation and characterization of a novel visible-light-responsive Rb2HgI4 nanostructure photocatalyst. Issue 49 (16th September 2021) - Abkar, Elham; Ghanbari, Mojgan; Amiri, Omid; Salavati-Niasari, Masoud
Abstract : In this study, we reported Rb2 HgI4 nanostructures as a new and efficient photocatalyst for the first time. We used the solid-state method for the fabrication of this compound at a low temperature. Abstract : Visible photocatalytic procedures exhibit encouraging potential in water purification by increasing the photocatalytic performance. Therefore, the improvement of low-cost and efficient photocatalysts for environmental remediation is an increasing demand, and photocatalysts based on semiconductors have gained considerable attention due to their superior stability and activity. In the current study, novel Rb2 HgI4 nanostructures were prepared via a simple, low-cost, and low-temperature solid-state method. The effects of different parameters such as type of surfactants, reaction temperature, and reaction time were studied on the structure, crystallinity, particle size, and shape of nanostructures. This new compound has a suitable band gap (2.6 eV) in the visible region. The photocatalytic performance of Rb2 HgI4 was examined for the removal of coloring agents under visible light irradiation and it was found that this compound could degrade and eliminate acid black 1 by about 72.1%.